The Pengaruh Pendapatan dan Pendidikan terhadap Kepuasan Pegawai Muda di PT Tri Nusa Abadi - Haris Abu Bakar Sidik (Muttaqien Publishing, Lembaga Penelitian dan Pengabdian kepada Mayarakat (P3M) STAI DR. KH.EZ. Muttaqien Purwakarta, 2023)
Income and education is one of the important factors that affect job satisfaction. Highly educated and well-earned individuals according to QS. Al-Mujadalah verse 11 sets high goals for career achievement and a good work ethic. High goals also reflect higher motivation and performance. Despite having a positive role in the organization, income and education also have a negative side. Individuals with income and education are fundamentally dissatisfied with their conditions and constantly want to significantly improve their working conditions. The study is intended to identify and analyze the impact education and income can have on the satisfaction of young employees in the PT. Tri Nusa Abadi. The method used in this study is the quantitative method. Income partially shows significant value (0.521 > 0.05) does not affect the satisfaction of young employees in PT. Tri Nusa Abadi. Results indicate a partial value of significance (0.01 < 0.05) education affects the satisfaction of young officers in PT. Tri Nusa Abadi. Simulated education and income indicate value of significance (0.00 < 0.05) affected the satisfaction of young employees in PT. Tri Nusa Abadi.